2020
DOI: 10.21873/invivo.12161
|View full text |Cite
|
Sign up to set email alerts
|

SMN Protein Contributes to Skeletal Muscle Cell Maturation Via Caspase-3 and Akt Activation

Abstract: Background/Aim: In spinal muscular atrophy (SMA), systemic deficiency of survival motor neurons (SMN) caused by loss or mutation of SMN1 leads to SMA symptoms. SMA was, for a long time, considered as a selective motorneuron disease. However, accumulated evidence suggests that skeletal muscle cells are affected by low levels of SMN protein. The purpose of this study was to elucidate the function of SMN protein in skeletal cell differentiation and maturation. Materials and Methods: In SMNΔ7 mice, which exhibit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…To understand the skeletal muscle-specific pathology, we examined Δ7-SMA mice on postnatal day 3 (P3), which is before the occurrence of motor neuronal deficits. The body weight of P3 Δ7-SMA mice was already decreased compared with WT, as previously reported ( Ando et al, 2020 ) ( Fig S6A ), indicating that skeletal muscle atrophy had already begun. The expression level of sarcomeric protein actinin Alpha 2 (ACTN2) also decreased in the tibialis anterior (TA), gastrocnemius (GA), and diaphragm of Δ7-SMA mice ( Fig 6A ), which is a hallmark of skeletal muscle atrophy ( Schiaffino et al, 2013 ).…”
Section: Resultssupporting
confidence: 87%
“…To understand the skeletal muscle-specific pathology, we examined Δ7-SMA mice on postnatal day 3 (P3), which is before the occurrence of motor neuronal deficits. The body weight of P3 Δ7-SMA mice was already decreased compared with WT, as previously reported ( Ando et al, 2020 ) ( Fig S6A ), indicating that skeletal muscle atrophy had already begun. The expression level of sarcomeric protein actinin Alpha 2 (ACTN2) also decreased in the tibialis anterior (TA), gastrocnemius (GA), and diaphragm of Δ7-SMA mice ( Fig 6A ), which is a hallmark of skeletal muscle atrophy ( Schiaffino et al, 2013 ).…”
Section: Resultssupporting
confidence: 87%
“…To understand the skeletal muscle-specific pathology, we examined Δ7-SMA mice on postnatal day 3 (P3), which is prior to the occurrence of motor neuronal deficits. The body weight of P3 Δ7-SMA mice was already decreased compared to WT, as previously reported (Ando et al, 2020) ( Figure S6A ), indicating that skeletal muscle atrophy had already begun. The expression level of sarcomeric protein actinin Alpha 2 (ACTN2) also decreased in the tibialis anterior (TA), gastrocnemius (GA) and diaphragm of Δ7-SMA mice ( Figure 6A ), which is a hallmark of skeletal muscle atrophy (Schiaffino et al, 2013).…”
Section: Resultssupporting
confidence: 87%
“…Survival motor neurons 1 and 2 (SMN1/2) are downregulated in both proliferating and differentiated muscle cells twofold. Deficiency of SMN1/2 is usually associated with spinal muscular atrophy; however, it was shown that low levels influence muscle differentiation and maturation through the AKT signalling pathway [65]. Similar involvements in proliferation, apoptosis and differentiation are known for many of the genes displayed in Figure 5.…”
Section: Splicing As the Basis Of Pathway Alterationsmentioning
confidence: 82%